Implementasi Game-Based Learning melalui Kahoot dalam Pembelajaran Sejarah SMP: Sebuah Kajian Literatur - Emilia Kurniawati; Sulastri Rini Rindrayani (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This study aims to describe the implementation of game-based learning through the Kahoot platform as a form of learning innovation in the digital era, especially in history teaching at the Junior High School (SMP) level. In the era of the Kurikulum Merdeka, which emphasises differentiated and participatory learning, the use of interactive digital media is a strategic solution in increasing student engagement and motivation to learn. Kahoot, as a game-based quiz platform, offers interactive features that teachers can utilise to deliver material engagingly, conduct formative evaluations, and create a fun and competitive learning environment. This study was compiled using a descriptive approach through a literature review from various scientific sources related to the use of Kahoot in learning. The results of the survey indicate that implementing Kahoot can increase students' enthusiasm, enhance their understanding of the material, and foster the development of 21st-century skills, including collaboration and digital literacy. Additionally, the technical steps for using Kahoot, including account creation, quiz design, and student participation, are explained in detail to provide educators with practical guidance. Thus, the integration of Kahoot in history learning is considered relevant and effective as part of an adaptive and meaningful digital education transformation.